Microsite selection and survival of greater sage‐grouse nests in south‐central Wyoming. Issue 5 (29th March 2016) - Hansen, Christopher P.; Schreiber, Leslie A.; Rumble, Mark A.; Millspaugh, Joshua J.; Gamo, R. Scott; Kehmeier, Jon W.; Wojcik, Nate
ABSTRACT: Greater sage‐grouse ( Centrocercus urophasianus ; hereafter, sage‐grouse) populations have declined across North America because of degradation of sagebrush ( Artemisia spp.) ecosystems; thus, management for sage‐grouse habitat is a high priority. Expansion of some energy development has put additional pressures on sage‐grouse populations and their habitats. However, little is known about the effects wind energy development may have on sage‐grouse populations. Population dynamics of sage‐grouse are partially related to nest success, which may be influenced by the quality of nesting habitat. Consequently, knowledge of vegetation and structural characteristics associated with selection and survival of sage‐grouse nests would help inform management decisions to improve nest success. As part of a study quantifying greater sage‐grouse demographics prior to construction of a wind energy facility, we monitored female sage‐grouse equipped with 30‐g solar Argos global positioning system platform transmitter terminals during the breeding season in Carbon County, Wyoming to assess selection and survival of nests at nest area (30‐m radius), nest patch (5‐m radius), and nest bowl scales. Sage‐grouse selected nest sites with increased visual obstruction from 22.9–45.7 cm in height at all scales, less forb cover at the nest area, and more sagebrush cover at the nest patch. Survival of nests to 27 days (i.e., incubation period) was 43.3% (95% CI: 31.8–59.1%) in 2011 ( n = 49), 33.2% (95% CI: 21.5–51.3%) in 2012 ( n = 40), and 25.1% (95% CI: 15.0–42.0%) in 2013 ( n = 39). Grass height had a positive association with survival of nests at the nest area and nest patch, canopy cover of bunchgrasses and sagebrush had an interactive effect on survival of nests at the nest patch, and visual obstruction from 0–22.9 cm in height had a positive relationship with survival of nests at the nest bowl. The standardized precipitation‐evapotranspiration index (SPEI), an index of drought, from the previous growing season was also negatively correlated with survival of nests. Our results suggest management for nesting sage‐grouse should focus on a heterogeneous compilation of tall bunchgrasses >15 cm and patches of sagebrush cover >30%. Management for grasses >15 cm tall should be especially diligent during drought years, given SPEI was associated with nest survival the following year. Although there could be other factors important to selection or survival of nests that we did not evaluate, our results suggest scale‐dependent management strategies at the microsite level may not be necessary. We encourage researchers and managers to use our baseline results in a before–after control‐impact design with future, post‐construction data to determine the potential effects of wind energy development on selection and survival of sage‐grouse nests. © 2016 The Wildlife Society.